TELEVISION'S INFLUENCE ON EATING HABITS, PRACTICES AND BEHAVIOR - Cíntia da Conceição Santos; Rosamary Aparecida Garcia Stuchi; Cristina Arreguy-Sena; Nísia Andrade Villela Dessimoni Pinto (Universidade Federal do Paraná, 2012)
This observational and descriptive study aimed to analyze the number and the timetabling of television adverts for food products, to classify them according to the Food Guide Pyramid, and to identify the calorie content of the most heavily-advertised, based on the nutritional information on their packaging. The primary data was collected from recordings of programs from two Brazilian free-view TV companies, from between July and December 2008, from the periods of morning, afternoon and evening, over twenty-eight days, and was analyzed according to frequency and content using Thayer's communication system. 239 adverts were identified in the 336 hours of the recordings. 85% of the products were in the pyramid group represented by sweets and fats; a total absence of fruits and greens was observed. This study indicates the need for employing educational strategies including the use of television for promoting the adoption of healthier eating habits.